Yacon (Smallanthus sonchifolius) peel as a promising peroxidase source for the treatment of phenolic wastewater - Souza D.H.* (2022)
© 2021 Elsevier LtdPeroxidases are versatile enzymes that catalyse the oxidation of many inorganic and organic substrates. There are numerous vegetable sources of peroxidases, including the yacon (Smallanthus sonchifolius), an easy-to-grow plant. This study aimed to extract, purify and characterise the peroxidases obtained from yacon roots. We partially purified the enzyme from yacon pell using an aqueous two-phase system (ATPS) and obtained 4.66 purification-fold and 33.87% activity recovery. The enzyme showed an optimal temperature of catalysis 60 °C and optimal pH 11 using pyrogallol as substrate. Considering the oxidation of 2,4-dichlorophenol, these conditions were 37.5 °C and pH 7. Furthermore, the enzyme presented substrate inhibition at high hydrogen peroxide concentrations. The presence of 5 mM Cu2+ inhibited, while and 5 mM Co2+ activated the enzyme. The enzyme remained stable at 50 °C for 60 min and showed improved thermostability compared to horseradish peroxidase. The kinetic mechanism of yacon peroxidase was investigated, and our studies suggested the enzyme follows a Ping-Pong Bi–Bi mechanism. Finally, 2,4-dichlorophenol was selected as a target pollutant, and we obtained as many as 86.26% of bioconversion using yacon peroxidase. The results presented in this article suggest that yacon is a promising source of peroxidase and can be an alternative for bioprocesses applications.